Design And Implementation Of An Mqtt-Based Internet Of Drone Things For Swarm Drone - Sari, Ratna; Karna, Nyoman Bogi Aditya; Irawan, Arif Indra (eProceedings of Engineering, 2023)
Swarm drones are drones that communicate witheach other, the more drones that communicate, the heavier thecommunication network, therefore the aim of this research is tobe able to make light communication between two drones usingthe Message Queuing Telemetry Transport (MQTT) dataprotocol. This thesis uses NodeMCU tools. The protocol used isMQTT in the use of communication between drones. Because ofthe shortcomings of the HTTP protocol, the MQTT serverprotocol must be implemented to support the development of theIoT platform. MQTT is a lightweight and simple communicationprotocol. The plan outcome is that two drones will be able tocommunicate reliably utilizing the MQTT data protocol. Afterconducting the test, the results of testing network quality with QoSparameters are delay, jitter, packet loss, and throughput. Theaverage delay of MQTT QoS 0 is 0.103 s, MQTT QoS 1 is 0.111s, and HTTP is 0.124 s. HTTP and MQTT QoS 0 get 0% packetloss, while MQTT QoS 1 gets 0.1% packet loss. Throughput on theMQTT protocol is faster than the HTTP protocol. And the networkquality of the MQTT protocol is better than HTTP.Keyword— MQTT,HTTP, IoT, Subscribe, Publish andBroker